PENDEKATAN HOLISTIK PADA NY. M UMUR 59 TAHUN DENGAN DIABETES MELLITUS TIPE 2 MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS TANJUNG SARI NATAR - Yahmal, Putri; Zuraida, Reni (CV. Jasa Sukses Abadi, 2024)
Data from the International Diabetes Federation (IDF) in 2021, the number of people with Diabetes Mellitus (DM) in the world reached 537 million adults. Indonesia is ranked 7th with 10.7 million. Lampung Province in 2021 there is an increase in the prevalence of DM to 88,518 people. The aim of application of Evidence Based Medicine (EBM) based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on the patient problem solving framework with a patient centered and family approach. This study analysis is a case report. Primary data were obtained through anamnesis (autoanamnesis), physical examination and home visits to complete family data, psychosocial and environmental data. Assessment was done based on holistic diagnosis from the beginning, process and end of the study quantitatively and qualitatively. Patient Mrs. M, 59 years old has internal risks, the patient rarely exercises, physical activity is relatively light, taking medicine irregularly, overweight nutritional status, Nutritional Adequacy Level (TKG) is less, still consuming foods that are not recommended for DM patients (consumption of fried foods), and lack of knowledge. Management of patients is holistic and comprehensive, patient-centered, family approach, and community-based in literature based on EBM. Patients were intervened with material in the form of power points. Patients experienced an increase in knowledge by 50 points, a decrease in blood sugar levels by 103 mg/dL and changes in patient behavior to consume food according to TKG.